2021
DOI: 10.3390/jpm11121252
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios as Predictors of Occult Cervical Metastasis in Clinically Negative Neck Supraglottic and Glottic Cancer

Abstract: Background. Among patients with diagnosis of Laryngeal Squamous Cell Carcinoma (LSCC), up to 37.5% of cases may have occult metastasis (OM), and this feature is linked to poor prognosis and high rate of local recurrence. The role of elective neck dissection (END) in clinically negative neck (cN0) LSCC remains controversial. It is of great value to search for low-cost and easily detectable indicators to predict the risk of OM in laryngeal cancer. Recent reports have shown that high values of the neutrophil-to-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Systematic inflammation indicators, which can be directly measured from blood test results, have been reported to be prognostic in multiple HNC subtypes. For example, pre-treatment neutrophil-to-lymphocyte ratio (NLR) has been investigated, and a strong statistical correlation was observed with positive neck occult metastasis in laryngeal squamous cell carcinoma [35]. Another study by Orabona et al confirmed the independent prognostic power of the systemic immune-inflammation index (SII) and the systemic inflammation response index (SIRI) on OS of patients who received malignant salivary gland tumor surgery [36].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic inflammation indicators, which can be directly measured from blood test results, have been reported to be prognostic in multiple HNC subtypes. For example, pre-treatment neutrophil-to-lymphocyte ratio (NLR) has been investigated, and a strong statistical correlation was observed with positive neck occult metastasis in laryngeal squamous cell carcinoma [35]. Another study by Orabona et al confirmed the independent prognostic power of the systemic immune-inflammation index (SII) and the systemic inflammation response index (SIRI) on OS of patients who received malignant salivary gland tumor surgery [36].…”
Section: Discussionmentioning
confidence: 99%
“…For MSGTs, the literature has already widely discussed the topic and has identified the following as valid prognostic factors: tumor grading, lymph node involvement, positive resection margins, and TNM staging, with the latter representing the most effective prognostic factor 25 . However, as reported by several authors, patients with the same TNM stage may still display different disease progression 5‐12 …”
Section: Discussionmentioning
confidence: 99%
“…25 However, as reported by several authors, patients with the same TNM stage may still display different disease progression. [5][6][7][8][9][10][11][12] Hence, the need to identify early prognostic indicators, that can effectively and inexpensively predict disease progression, is paramount.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, immunological biomarkers for predicting prognostic information were provided, to facilitate clinical decision-making [12]. In spite of all the literature demonstrating the association between lymph node status and inflammatory indices (especially neutrophil-to-lymphocyte ratio [NLR]) [13,14], only a little evidence has described the association of NLR with pathological lymph node status in a population clinically N0, in oral and laryngeal cancer only [15][16][17][18]. To our knowledge, this focus on clinically occult metastases has never been replicated in the setting of oropharyngeal or hypopharyngeal HNSCC.…”
Section: Introductionmentioning
confidence: 99%